Nonalcoholic fatty liver disease after pancreatoduodenectomy is closely associated with postoperative pancreatic exocrine insufficiency. Issue 6 (25th June 2014) - Nakagawa, Naoya; Murakami, Yoshiaki; Uemura, Kenichiro; Sudo, Takeshi; Hashimoto, Yasushi; Kondo, Naru; Sasaki, Hayato; Okano, Keisuke; Sueda, Taijiro
<x xml:space="preserve">Abstract</x> Background In recent years, nonalcoholic fatty liver disease (NAFLD) after pancreatoduodenectomy (PD) has become increasingly problematic. Our aims were to clarify the relationship between NAFLD and postoperative pancreatic exocrine function and to identify the risk factors for NAFLD after PD. Methods Patients who underwent PD (n = 104) were assessed with abdominal unenhanced computed tomography (CT) to determine the fatty liver changes and were given a 13C‐labeled mixed triglyceride breath test to measure pancreatic exocrine function. The percent 13CO2 cumulative dose at 7 hr (% dose 13C cum 7 hr) <5% was considered diagnostic for pancreatic exocrine insufficiency (PEI). Relationships between the occurrence of NAFLD and clinical factors including postoperative pancreatic exocrine function were analyzed. Results Twenty‐six of 104 patients (25%) developed postoperative NAFLD. The postoperative CT attenuation of the liver (R = 0.326, P < 0.001) and the liver‐to‐spleen attenuation ratio (R = 0.315, P = 0.001) significantly correlated with the postoperative values of % dose 13C cum 7 hr. Multivariate analysis determined that postoperative PEI was the only independent risk factor for NAFLD (P = 0.025). Conclusions NAFLD frequently occurs postoperatively after PD. NAFLD after PD may be closely associated with postoperative PEI. J. Surg. Oncol. 2014 110:720–726. © 2014 Wiley Periodicals, Inc.